Undermining Assessment: EIA follow-up, stake-holder advisory groups, and extractive industries in Nunavut, Canada. Issue 2 (4th March 2023) - Bernauer, Warren; Hostetler, Glen; Greene, Ezra; Tester, Frank; Harris, Rowan; Tanguay, Laura
ABSTRACT: This paper contributes to the literature about environmental impact assessment follow-up, with case studies of stakeholder advisory groups associated with three mining projects in Nunavut, Canada. Based on an analysis of regulatory documents, we conclude that stakeholder advisory groups, as constituted and currently operating in Nunavut, are undermining aspects of the environmental assessment process. For example, potential impacts to wildlife that are invaluable to Inuit communities, as well as proposed measures to mitigate these impacts, have repeatedly been deferred to post-approval discussions in advisory groups. As a result, potential impacts and proposed mitigations are not adequately assessed during decision-making and permitting. Opportunities for public participation are curtailed, as advisory groups have no mechanism for public involvement and suffer from limited transparency. Moreover, these advisory groups have proven to be ineffective forums for guiding post-approval monitoring and addressing project effects. Other jurisdictions can learn from these experiences. A failure to implement best practice principles and stakeholder advice can lead to negative social and ecological outcomes.